The Role of the Respiratory Intermediate Care Unit in Interstitial Lung Disease Exacerbations: A Bridge to Lung Transplantation - Ainhoa Izquierdo Pérez; Silvia Aguado Ibáñez; Sonia Salinas Castillo; Gabriela Pombo Lacaba; Enrique Rodríguez Rubio; Rosalia Laporta Hernández; Beatriz Jara Chinarro; Carlos Almonacid Sánchez (Open Respiratory Archives)
Introduction: This study aims to describe the clinical features, hospital management, and outcomes of patients with interstitial lung disease (ILD) and acute respiratory failure (ARF) admitted to the respiratory intermediate care units (RICUs). Material and methods: An observational study was conducted on ILD patients admitted to the RICU between June 1, 2021, and May 30, 2024. Main variables analysed included demographics, non-invasive respiratory support (NIRS) types, ILD-related variables, lung transplant outcomes, and survival rates. Results: Of the 401 patients admitted, 51 (13%) had ILD, of whom 34 (67%) were male. Idiopathic pulmonary fibrosis (IPF) was the most common condition (33%), and high-flow oxygen therapy (HFOT) was the primary treatment (94%). Infection (29%) and disease progression (36%) were the main hospitalization causes. Of the 27 patients (53%) evaluated for transplantation, 18 (36%) underwent a lung transplant, with 5 (28%) directly transplanted from the RICU and 55% (N = 15) were added to the emergency-driven list. Overall survival rates for ICU-eligible patients were 89% at one month, 77% at six months, and 72% at one year, while non-ICU eligible had lower survival probabilities of 31%, 13%, and 13%, respectively. Conclusions: The RICU should be considered a bridge therapy for patients who are ICU candidates and eligible for lung transplant during ILD exacerbations, potentially reducing ICU admissions. However, patients who are not ICU candidates face high short- and medium-term mortality risks. The significance of this study highlights the need to establish a specific RICU admission protocol for patients experiencing ILD exacerbations. Resumen: Introducción: Describir las características clínicas, el manejo hospitalario y el desenlace de los pacientes con enfermedad pulmonar intersticial difusa ingresados por insuficiencia respiratoria aguda en la unidad de cuidados intermedios respiratorios (UCIR). Material y métodos: Se llevó a cabo un estudio observacional de una cohorte de pacientes con EPID ingresados en la UCIR entre el 1 de junio de 2021 y el 30 de mayo de 2024. Las principales variables analizadas fueron demográficas, tipo de soporte respiratorio no invasivo, relacionadas con la EPID, el trasplante y la supervivencia. Resultados: De los 401 pacientes admitidos en UCIR al año, 51 (13%) tenían diagnóstico de EPID, siendo un 67% varones. La patología más frecuente fue la FPI (33%), y el SRNI más empleado fue la oxigenoterapia de alto flujo (OAF) en un 94%. Las causas más frecuentes de ingreso fueron infección (29%) y progresión de enfermedad (36%). De los 27 pacientes evaluados para trasplante, finalmente se trasplantaron 18 (36%), 5 (28%) directamente desde UCIR, y el 55% (n = 15) requirieron priorización a nivel nacional. La supervivencia global estimada de los pacientes candidatos a UCI al mes fue del 89%, a los 6 meses del 77% y al año del 72%, mientras que los pacientes no candidatos a UCI tenían menores probabilidad de supervivencia, siendo del 31%, del 13% y del 13%, respectivamente. Conclusiones: Las UCIR deben ser consideradas como puente al trasplante en pacientes candidatos a trasplante durante las exacerbaciones de EPID, para reducir ingresos en la UCI. Sin embargo, los pacientes con techo terapéutico UCIR enfrentan una mortalidad a medio y a corto plazo elevada. El presente estudio sirve como base para enfatizar la necesidad de crear protocolos específicos de ingreso en la UCIR en pacientes con exacerbación de EPID.